Profil Pasien Lupus Eritematosus Sistemik di RSUP Dr. M. Djamil Padang Tahun 2020-2021 - Akmal, Elfi Fauzana; Dwitya Elvira; Noverika Windasari; Malinda Meinapuri; Raveinal, Raveinal; Yulistini, Yulistini (EDUPEDIA Publisher, 2024)
Objective: To understand the profile of SLE patients at RSUP.Dr.M.Djamil Padang period of 2020-2021. Methods: The research is a descriptive type with a retrospective approach. Medical record data were collected using total sampling technique,189 samples met the inclusion criteria. Data analysis using Microsoft Excel. Results: The study found that the majority of characteristics include female patients (95.8%), age group 17-25 years (33.9%), housewives (41.8%), medium-level education (66.1%), and of Minangkabau ethnicity (86.8%). Most patients had a disease duration of ≥ 2 years (78.8%), mild disease activity (36%), the most common clinical manifestation being mucocutaneous involvement (82%). ANA Profile results, the most prevalent finding was positive dsDNA (25.4%). Patients meeting ACR 1997 criteria were 57.1%, SLICC 2012 35.4%, and EULAR 2019 10.6%. The most frequently therapy was a combination of HCQ and glucocorticoids (45%), while the most common patient outcome was survival (96.8%). Conclusion: Majority of SLE patients at RSUP Dr.M.Djamil Padang are in the productive age group with mild disease activity. The majority of patients have good outcome, indicating a favorable prognosis for SLE at RSUP Dr. M. Djamil Padang.